Perceived risks around choice and decision making at end-of-life: A literature review. (January 2013) - Wilson, F; Gott, M; Ingleton, C
Background: the World Health Organization identifies meeting patient choice for care as central to effective palliative care delivery. Little is known about how choice, which implies an objective balancing of options and risks, is understood and enacted through decision making at end-of-life. Aim: to explore how perceptions of 'risk' may inform decision-making processes at end-of-life. Design: an integrative literature review was conducted between January and February 2010. Papers were reviewed using Hawker et al.'s criteria and evaluated according to clarity of methods, analysis and evidence of ethical consideration. All literature was retained as background data, but given the significant international heterogeneity the final analysis specifically focused on the UK context. Data source: the databases Medline, PsycINFO, Assia, British Nursing Index, High Wire Press and CINAHL were explored using the search terms decision*, risk, anxiety, hospice and palliative care, end-of-life care and publication date of 1998–2010. Results: thematic analysis of 25 papers suggests that decision making at end-of-life is multifactorial, involving a balancing of risks related to caregiver support; service provider resources; health inequalities and access; challenges to information giving; and perceptions of self-identity. Overall there is a dissonance in understandings of choice and decision making between service providers and service users. Conclusion: the concept of risk acknowledges the factors that shape and constrain end-of-life choices. Recognition of perceived risks as a central factor in decision making would be of value in acknowledging and supporting meaningful decision making processes for patients with palliative care needs and their families.